[BP.08.03] HEART RATE DEPENDENCY OF REGIONAL AND LOCAL AORTIC PULSE WAVE VELOCITY IN RATS AS A FUNCTION OF BLOOD PRESSURE. (September 2017) - Spronck, B.; Tan, I.; Reesink, K.D.; Georgevsky, D.; Delhaas, T.; Avolio, A.P.; Butlin, M.
Abstract : Objective: Arterial stiffness, as measured by aortic pulse wave velocity (PWV), is a marker of cardiovascular disease, but is known to depend on blood pressure (BP). PWV can be quantified regionally by measuring the time difference of the arrival of the BP wave at two sites along the arterial bed (transit time; TT-PWV), or locally by combining measured arterial pressure and diameter using the Bramwell-Hill equation (BH-PWV). We have previously quantified the TT-PWV dependency on heart rate (HR) and BP in both rats and humans. However, the HR dependency of BH-PWV is yet unknown. The present study aimed to quantify the HR dependency of TT-PWV and BH-PWV, as functions of diastolic blood pressure (DBP). Design and method: Adult anaesthetised Sprague-Dawley rats (n = 5) were randomly paced at HRs of 300–500 bpm, at 50-bpm steps. At each step, aortic TT-PWV (two pressure-tip catheters) and BH-PWV (pressure-tip catheter and ultrasound wall-tracking; abdominal aorta) were measured simultaneously, across a DBP range of 60–110 mmHg as induced by intravenous sodium nitroprusside and phenylephrine infusion (both 30 μg/kg/min). BP wave arrival (TT-PWV) was determined using the maximum of the second-derivative of the BP waveform. After beat detection and segmentation, data from 1368 heart beats was analysed using mixed-effects modelling. Results: The effect of HR on TT-PWV is negligible at low DBP, but increases proportionally with DBP (Figure A). For BH-PWV the effect of HR is apparently zero at DBP = 85 mmHg, but positive at lower and negative at higher DBP (Figure B, black data). The decrease in BH-PWV with HR observed at DBP = 110 mmHg is explicable by the fact that the standard BH-PWV uses an approximate derivative of pressure to diameter, which overestimates PWV with increasing pulse pressure (PP). PP decreases as HR increases, potentially causing the BH-PWV decrease with HR (Figure C). This effect can be overcome by estimating the pressure-diameter curve for each HR, and calculating the true derivative at DBP (Figure D), yielding a BH-PWV that no longer shows significant HR dependency (Figure B, grey data). Figure. No caption available. Conclusions: BH-PWV and TT-PWV show different and even opposite HR dependency, depending on DBP.